Determinan Ekspor Kopi Indonesia: Berpengaruhkah FTA? - Putro, Fikri Aldi Dwi; Putri, Lovina Aresta; Prawira, Gunawan; Sahara, Sahara (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Indonesia has initiated trade liberalization to boost the coffee export performance in the international market through trade agreements (FTA). However, Indonesian coffee export performance tends to decline. This study aims to analyze the effect of Indonesia’s FTA with its trading partners and other determinants of Indonesian coffee exports. This research employs a modified export approach gravity model with PPML estimation. The result shows that the FTA implementation generally can promote Indonesian coffee export, implying the export creation effect. Therefore, inward and outward-looking strategies are necessary to further boost the export creation effect on Indonesian coffee.